2020
DOI: 10.1007/s00125-019-05083-6
|View full text |Cite|
|
Sign up to set email alerts
|

The role of physical activity in metabolic homeostasis before and after the onset of type 2 diabetes: an IMI DIRECT study

Abstract: Aims/hypothesis It is well established that physical activity, abdominal ectopic fat and glycaemic regulation are related but the underlying structure of these relationships is unclear. The previously proposed twin-cycle hypothesis (TC) provides a mechanistic basis for impairment in glycaemic control through the interactions of substrate availability, substrate metabolism and abdominal ectopic fat accumulation. Here, we hypothesise that the effect of physical activity in glucose regulation is mediated by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…As a result of physical inactivity, we observed small but significant changes in metabolic profiles and body composition that would predispose individuals to the development of metabolic syndrome and/or type 2 diabetes: a decrease in insulin sensitivity, increase in plasma triglycerides (0.2 mmol/L), loss of (lower limb) lean body mass and deposition of total body and liver fat (0.2%). In terms of the twin cycle hypothesis ( Taylor, 2008 ), it has been suggested that insulin sensitivity and liver fat mediate the association of physical activity with glycemic control ( Koivula et al, 2020 ). Our previous study showed that changes in insulin sensitivity were specific to skeletal muscle ( Bowden Davies et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of physical inactivity, we observed small but significant changes in metabolic profiles and body composition that would predispose individuals to the development of metabolic syndrome and/or type 2 diabetes: a decrease in insulin sensitivity, increase in plasma triglycerides (0.2 mmol/L), loss of (lower limb) lean body mass and deposition of total body and liver fat (0.2%). In terms of the twin cycle hypothesis ( Taylor, 2008 ), it has been suggested that insulin sensitivity and liver fat mediate the association of physical activity with glycemic control ( Koivula et al, 2020 ). Our previous study showed that changes in insulin sensitivity were specific to skeletal muscle ( Bowden Davies et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between habitual exercise and the twin cycle predictions was examined in the IMI DIRECT Study [83]. This cross-sectional study of people with type 2 diabetes demonstrated associations of exercise with both liver fat and liver insulin sensitivity according to the postulated liver cycle.…”
Section: Physical Activity Weight Loss and Weight Maintenancementioning
confidence: 99%
“…Using data from the UK Biobank, this study supports the hypothesis that individuals with diagnosed T2D exhibit physical activity patterns that are significantly different from those of normoglycemic controls, thus providing novel ways to detect T2D, that is, through appropriate analysis of physical activity patterns. Although most previous studies, particularly using UK Biobank, are limited to self-reported physical activity levels [ 5 , 11 , 25 ], here we have demonstrated the benefits of extracting a more objective and granular representation of physical activity from raw accelerometry traces data, namely, by activity type and time of day or sleep time. Using these features, either on their own or in combination with a selected set of sociodemographic, anthropometric, and lifestyle variables, we have shown that appropriately trained machine learning models were able to discriminate between the 2 cohorts with good predictive accuracy.…”
Section: Discussionmentioning
confidence: 82%